MEMBANGUN LOYALITAS NASABAH MELALUI KUALITAS RELASIONAL BERBASIS PADA MANFAAT-MANFAAT RELASIONAL YANG DIBERIKAN KEPADA NASABAH (Studi Empiris pada BPR Agung Sejahtera Semarang) (Proceeding Fakultas Ekonomi, 2011)
med to examine the influence of Social benefits, Special Services benefits, Trust' benefits in customer satisfaction, customer satisfoction to the next customer commitment, and how it impacts the customer's commitment to positive WoM communication and Customer Loyalty. This study  focused  Rural Semarang, which has been a customer  on the customer's credit in the Great Prosperous over a year. Purposive sampling technique was taken on the grounds that: the respondents had sufficient experience with a relationship for  banh so it can answer the questions posed. The number of respondents that can be processed in this study amounted to I2l people. Processing the data using SPSSfor Windows Ver.16. The results showed that there are tvvo hypotheses are rejected, the hypothesis of the impact of the bene;fits of dedicated service to the customer satisfaction (h2) and the impact oJ'positive ,'t/OM communication to Loyalty (H7). As for  hypothesis: Social Benefits, and Trust in customer satisfaction (hl, h3) proved significant; Effict of Customer Satisfaction on Customer Commitment (h4) also proved significant, and commitment to positive WOM communication(h5) and Loyalty (h6) also proved significant. Each of inJluence between these variables showed a positive direction. So the results of this study prove that loyalty and positive WoM communication can be built from  the Customer Commitment, and Customer Commitment can be achieved if customers are satisfied and is essentially a relational benefits, namely: social benefits and trust benefits perceived by customers.Key word: Relational Benefits, Customer Satisfaction, Customer Commitment, Positive WOM Communication, and Customer Loyalty